ADA APA DENGAN I SUGIH TINJAUAN KOMPARASI PSIKOLOGI I SUGIH DAN I TIWAS. - Ni Made Ayu Susanthi Pradnya Paramitha; Ni Kadek Meidita Dwi Yanti; Ni Putu Putri Aryaningsih; Ida Bagus Putu Pratama Kumara Wisesa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
As a representation of the human psyche, literature often highlights women's issues. The phenomenon of female hegemony remains prevalent and continues to be a relevant topic of discussion across time. This condition is also reflected in a Balinese folktale (satua) titled I Sugih teken I Tiwas. Interestingly, I Sugih, portrayed as a wealthy woman (sugih), is unable to free herself from feelings of envy toward I Tiwas, a poor woman (tiwas). Why does I Sugih, despite her wealth, treat I Tiwas so poorly? I Tiwas poses no real threat to I Sugih, especially in terms of material wealth. Yet, economic dominance alone does not guarantee psychological well-being for I Sugih. What is truly going on with I Sugih? This question is explored through a comparative analysis of psychological needs fulfillment between I Sugih and I Tiwas, based on Abraham Maslow’s hierarchy of needs theory and using a descriptive qualitative method. The results show that the fulfillment of psychological needs is more complete in the character of I Tiwas than in I Sugih.